The future-climate, current-policy framework: towards an approach linking climate science to sector policy development. (23rd November 2020) - Evans, Barbara E; Rowell, David P; Semazzi, Frederick H M
Abstract: That global climate is being altered by human activities is well-established; for specific locations, however, the details of how and when many aspects of the changes will become manifest remains somewhat uncertain. For many policy makers there is a gap between recognising a long-term change and implementing short-term practical responses; therefore many countries are failing to implement changes needed for long-term adaptation. Traditional planning approaches are often closely aligned with near- term political cycles and perform poorly in terms of prioritising interventions that address multi-decadal climate impacts. We propose a novel approach that builds on adaptive planning and lessons from the business sector. The Future-Climate, Current-Policy (FCCP) Framework is based on plausible medium-term future climate scenarios, linked 'backwards' to identify short-term 'no regrets' actions. The approach was designed by a team of climate scientists and policy practitioners in East Africa and tested in national and regional fora. Initial trials of the FCCP Framework has proved it to be popular and effective as a way of linking climate science with policy. Its use shows promise as a way of initiating discussions that can enable long-term climate change information to feed effectively into the policy and planning process.